(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Purpose: This study examines the intellectual evolution of the toy industry through a domain-based Systematic Literature Review (SLR). The review is guided by four research questions: (RQ1) What are the publication trends in toy-related research? (RQ2) What thematic clusters define the intellectual structure of the toy domain? (RQ3) How do policy and economic developments influence the evolution of the toy industry? and (RQ4) What future research directions emerge from existing literature? Research Design: The review follows PRISMA 2020 guidelines and the SPAR-4-SLR protocol. Peer-reviewed articles were systematically retrieved from the Scopus database to capture historical developments and structural shifts within the toy industry. Bibliometric techniques were applied using Biblioshiny (R) and VOSviewer, including descriptive analysis, keyword co-occurrence mapping, cluster analysis, and factorial analysis (PCA). Key Findings: The findings reveal a steady Compound Annual Growth Rate (CAGR) of 6.65% in toy-related research. The literature is organized into ten thematic clusters, which merged together as three core areas such as; core toys, smart and digital toys and toy production & design, . Keywords related to data-driven technologies, such as deep learning, machine learning, and IoT, appear prominently, reflecting the growing integration of digital and analytical tools within toy research. Recent studies increasingly focus on wooden toys, smart toys, and technology-enabled play products. Originality and Implications: To the best of the authors’ knowledge, this is the first domain-wide bibliometric review of the toy industry. The study offers a structured understanding of research trends and thematic evolution, providing useful insights for scholars, industry practitioners, and policymakers. The findings support evidence-based decision-making for innovation, policy formulation, and future academic inquiry in the toy sector. The findings will also help governments, startups to identify the core changes of the toy industry in recent years, which will help the government to make a policy framework; practitioners to identify new trends and clusters.